(untitled) (Indian Journal of Child Health, 2016)
Progressive pseudo rheumatoid dysplasia (PPRD) is an autosomal recessive skeletal dysplasia with an underlying mutation in WISP 3 gene. Clinical, it is frequently misdiagnosed as juvenile idiopathic arthritis (JIA), particularly the seronegative polyarticular JIA. It is the characteristic radiological feature which helps in the early recognition of this disease. Here, we report a case of PPRD which has been previously diagnosed as JIA and was on antirheumatoid drugs with no improvement rather a progressive course. Because of its resemblance, PPRD should be kept in mind in the differential diagnosis of inflammatory joint diseases and metabolic bone diseases to prevent inappropriate treatment and unnecessary investigation.